RETRACTED: Possibilities of applying the technology and stages of implementing artificial intelligence in the modern economy - Barsukova N. V.; Morin K. A.; Lozovaya O. V.; Chivileva I. V.; Martynushkin A. B.; Polyakov M. V. (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001